Penerapan Metode Jaringan Syaraf Tiruan Untuk Meramalkan Kapasitas Layanan Pada Jasa Perawatan Sepatu (Studi Kasus Sepatu Bersih) - Sandy Ikhsan Armita; Nurul Hidayat; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Shoe treatment business is a sub business from developing conventional laundry with more complex and specific technic. This kind of business is a new one for the market, because all they know how to treat their shoe is just by washing it regularly. Actually the market potential for this business is promising, because shoe is daily essential for everyone's activity and of course it's part of the appearance to make a better looks. This business was known by the market in the early 2009, it was started by some accounts offering their service on the forum such as Kaskus, till the early 2012 this business has a bigger market due to the education of the people. The technic, tools, and stuff for shoe treatment had to be advance. By the time because of gaining demand of the market, the competition in this business is getting real. There so many business had to close too soon because cant do the strategical business plan, one of it was how to predict the service capacity. Therefore from that problem there is a method that could be useful for predicting the service capacity, using the Artificial Neuron Network method. By counting the process from the backpropagation and looking for the smallest output is 0,01616 of MSE to decide the most accurate number of the prediction.